The Implementation of the Independent Curriculum (Merdeka Curriculum) in the ‘Independent Change’ and ‘Sharing’ Phases in Pancasila Education at the Primary School Level: Implementasi Kurikulum Merdeka Mandiri Berubah dan Berbagi Pada Pembelajaran Pendidikan Pancasila Di Pendidikan Dasar - Yusuf Khoiril Anwar; Muzdalifah; Agus Retnanto (Al Kautsar: Knowledge Advancements in Teaching Strategies and Research, 2025)
The Merdeka Curriculum is Indonesia’s national curriculum replacing the 2013 Curriculum, characterized by flexible implementation categories and the establishment of Pancasila Education as a subject distinct from Civic Education. This study aims to analyze the implementation of the “Independent Change” and “Independent Sharing” categories in Pancasila Education at MIN 1 Rembang and SDI Umar Harun Sarang. This research employs a qualitative case study approach. Data were collected through observation, interviews, and document analysis, and validated using triangulation techniques. The findings indicate that the implementation in both schools follows stages of planning, implementation, evaluation, and reflection. In the “Independent Change” category, teachers act as organizers, facilitators, evaluators, and reflectors, while students tend to be passive executors and processors. Supporting factors include learning methods, media use, and material integration, whereas inhibiting factors involve low student confidence and weak group collaboration. In the “Independent Sharing” category, teachers take on roles as facilitators, leaders, and disseminators of best practices, while students actively participate as planners, collaborators, and evaluators. Supporting factors include school culture, classroom agreements, and leadership support, while challenges relate to limited external reinforcement, classroom conditions, and teacher adaptation.